Design and use of virtualization technology in cloud computing - Das, Prashanta Kumar; Deka, Ganesh Chandra 1969- (IGI Global, 2017)
"This book covers deep survey for Virtualization Technology and focus on issues and challenges related to Virtualization with its practical implication for education and software Industry. It describes architectural design of Hypervisor or VMM used for virtualization, the repercussion of cloud computing, grid computing and mobile computing using virtualization"...